Preparation and Properties Study of Cr on FeCrAl Cladding Materials - Wang, Peng; Qiao, Yingjie; Qi, Wen; Du, Shiyu; Liu, Zhen; Meng, Fanping; Zhang, Xiaohong; Wang, Kun; Li, Qiuwu; Yao, Zhaoding; Bai, Chengying; Wang, XiaoDong (Frontiers in Materials, 2021)
FeCrAl alloy is a promising candidate material for the fourth-generation reactor core cladding material. Adjustment of the Cr content is one of the effective ways to obtain enhanced performance for the FeCrAl alloy. In this work, Fe–xCr–6Al alloy (11 ≤ x ≤ 15) with different Cr content were successfully prepared by hot rolling. When Cr replacement of Fe atoms in Fe–xCr–6Al alloy rises from 11 to 15wt%, the lattice distortion of Fe–xCr–6Al alloy increases, and the mechanical properties and thermal conductivity of the Fe–xCr–6Al alloy are raised. Compared with Al content, Cr content has less effect on Fe–xCr–6Al oxidation resistance.